International Experiences in Diversifying Sources of National Income: Lessons for Libya - Ahmed Elgomaty, Helmi (Dirasat in Economics and Business, 2026)
This study investigates international experiences in diversifying national income sources to offer insights for Libya’s economic development. Employing a descriptive-analytical approach, the research analyzes time series data from 2007 to 2022 using simple regression to examine the relationship between various Libyan export categories and gross domestic product (GDP). The findings confirm a positive correlation between GDP and exports of primary agricultural materials, food, oil, and gas. The study advocates for enhancing the efficacy of Libya’s financial and monetary policies to stimulate tangible economic growth. It further emphasizes the importance of increased government investment in sectors that foster rapid economic development while ensuring the sustainability of achieved growth rates. Crucially, the study underscores the need for diversifying Libya’s income streams to reduce reliance on oil and recommends developing economic and financial policies that support this objective.